Environmental sustainability in Malaysia: efforts so far and challenges ahead - Kadouf, Hunud Abia; O. Sambo, Abdulfatai (Kaerntner Botanikzentrum, Klagenfurt, Austria, 2014)
Being a developing country which hopes to join the developed nations by 2020, environmental sustainability has been at centre stage in Malaysia. Which efforts are being made to promote economic development, these economics activities seem to be having its side effects on the protection of the environment. Nevertheless, there are also mechanisms being put in place to achieve sustainable pollution free environment. These have been in terms of conclusion of treaties and enactment of legal, regulatory and policy framework towards ensuring environmental sustainability. Based on this premise, this paper is intended to evaluate the efforts so far taken and the challenges which serve as stumbling block to proper realisation of environmental protection objective. A number of treaties, conventions, enactments, regulations and judicial pronouncements are used to enrich this study. The paper finds that a lot of legal, policy and regulatory frameworks have been created to ensure environmental protection. Yet, the challenges to proper implementation of these frameworks are enormous though surmountable.